2017
DOI: 10.3389/fcimb.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Inactive trans-Sialidase Expression in iTS-null Trypanosoma cruzi Generates Virulent Trypomastigotes

Abstract: Disclosing virulence factors from pathogens is required to better understand the pathogenic mechanisms involved in their interaction with the host. In the case of Trypanosoma cruzi several molecules are associated with virulence. Among them, the trans-sialidase (TS) has arisen as one of particular relevance due to its effect on the immune system and involvement in the interaction/invasion of the host cells. The presence of conserved genes encoding for an inactive TS (iTS) isoform is puzzlingly restricted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In relation to gp85/transsialidase, San Francisco and colleagues [40] demonstrate that this protein plays a fundamental importance in invasion since its depletion causes a decrease in T. cruzi virulence. The same type of result was reported by Pascuale et al [41] since inactive TS expression in trypomastigotes of a strain that does not express these TS (iTS null) allowed a better invasion and increase of the parasitic load in mice demonstrating that the inactive form may act alternatively or complementing the active TS in pathogenesis.…”
Section: T Cruzi Trypomastigote-host Cell Recognitionsupporting
confidence: 81%
“…In relation to gp85/transsialidase, San Francisco and colleagues [40] demonstrate that this protein plays a fundamental importance in invasion since its depletion causes a decrease in T. cruzi virulence. The same type of result was reported by Pascuale et al [41] since inactive TS expression in trypomastigotes of a strain that does not express these TS (iTS null) allowed a better invasion and increase of the parasitic load in mice demonstrating that the inactive form may act alternatively or complementing the active TS in pathogenesis.…”
Section: T Cruzi Trypomastigote-host Cell Recognitionsupporting
confidence: 81%
“…A comparative transcriptome profiling revealed that the CL-14 T. cruzi clone, which shows reduced expression of gene families encoding surface proteins-such as trans-sialidases and mucins-is associated with a nonvirulent phenotype (46). Likewise, transfection of noninfective T. cruzi strains with virulence factors such as inactive trans-sialidases leads to the generation of infective trypomastigotes (55). These findings strongly suggest that RBPs are involved in the modulation of expression of virulence factors affecting T. cruzi infectivity.…”
Section: Coordinated Regulation Of Multiple Mrnas In T Cruzimentioning
confidence: 99%
“…However, it should be noted that these proteins could have other functions, as has been described for the trans-sialidase family, a family that should be renamed because most of its members have no enzymatic activity due to a mutation in the active site (26). However, these proteins retain other important functions by facilitating interaction with host cell receptors, promoting signaling and cell invasion of trypomastigote forms (27).…”
Section: -Signal and Domain Recognition In Predicted Gp63 Amino Acid ...mentioning
confidence: 99%